Irigenin inhibits glioblastoma progression through suppressing YAP/β-catenin signaling - Xu, Jiayun; Sun, Shanshan; Zhang, Wei; Dong, Jianhong; Huang, Changgang; Wang, Xin; Jia, Mengxian; Yang, Hao; Wang, Yongjie; Jiang, Yuanyuan; Cao, Liying; Huang, Zhihui (Frontiers in Pharmacology, 2022)
Glioblastoma (GBM) is the highest degree of malignancy among gliomas in brain tumors with low survival and high recurrence rate. Irigenin, as an isoflavone compound extracted from Shegan, has shown many pharmacological functions such as antioxidant, anti-inflammatory and anti-tumor. However, the effects and molecular mechanisms of irigenin in GBM cells remain unexplored. In this study, we found that irigenin inhibited the proliferation of GBM cells in a dose-dependent manner by several assays in vitro. Subsequently, we demonstrated that irigenin inhibited the migration and induced apoptosis of GBM cells in vitro. In addition, irigenin induced G2/M cell cycle arrest in GBM cells. Mechanically, we used molecular docking, and a combination of Western blot and immunostaining experiments to show that irigenin treatment decreased the expression of YAP (yes-associated protein), suppressed β-catenin signaling. Furthermore, overexpression of YAP partially restored the anti-tumor effects of irigenin on GBM cells in vitro. Finally, we found that irigenin could inhibit the growth of tumor in GBM xenograft mouse model through inactivation of YAP. Taken together, these results suggest that irigenin exerts its anticancer effects on GBM via inhibiting YAP/β-catenin signaling, which provides a new strategy for the treatment of GBM.